Iu Mien Tribe Child Rearing Culture - แซ่ลิ่ว, จันทรา (Community and Social Development Journal, 2018)
This research aims to study the culture of early childhood education of the Iu Mien ethnic group. A total of 65 samples were selected from the sample group consisting of 20 Iu Mien mentors and 45 early childhood parents. The tools used in the study were in-depth interviews, informal interviews, participatory observation and non-participant observation. This research was a Qualitative research using descriptive analysis. The result showed that the Iu Mien have changed in economic terms, society and physical structure are quite modern. This affects the preparation of family planning, ie, marriage and childbearing when it comes to health and the economy. Unlike the past, they would have the child immediately after marriage and young. In the life and early childhood education of the Iu Mien are associated with culture, traditions, rituals and beliefs that have long been inherited. Iu Mien parents will be raising children together without separate duties. Use democratic parenting and abandonment schemes in some families. Bring knowledge from various sources for example from the teachings of the elders, from the advice of the doctor, in the book, etc. in parenting and promoting development coupled with parenting based on culture, traditions, rituals and beliefs inherited from the ancestors to encourage children to grow, develop well and be able to support their families when they grow.